On Fundamentos de defectología and the development of Special Education teachers in Brazil - Costas, Fabiane Adela Tonetto; Selau, Bento (Educação, 2018)
This text aimed at confirming whether the book Fundamentos de defectología (VYGOTSKI, 1997) constitutes the official documents that compose the National Policy on Special Education from the Perspective of Inclusive Education, issued by SECADI/MEC/Brazil. A search was conducted on its official didactic materials but this book was not found. A new search revealed that it was used as a reference to post-graduate final projects (three Master’s thesis and a doctoral dissertation), to Research Groups n. 15 – Special Education – and n. 20 – Psychology of Education – at ANPEd (a research and three discussion texts) and to books and journals (two book chapters and nine articles published by journals), totaling nineteen studies. Two of them refer to the book in the area of Teacher Education, specifically in specialized educational assistance, suggesting that it has been poorly disseminated in continuing Teacher Education. *** Fundamentos de defectología e a formação de professores de Educação Especial no Brasil *** Este texto buscou confirmar se a obra Fundamentos de defectología (VYGOTSKI, 1997) constitui os materiais oficiais da SECADI/MEC/Brasil a partir da Política Nacional de Educação Especial na Perspectiva da Educação Inclusiva. Realizou-se pesquisa nos materiais didáticos oficiais, não sendo observada esta obra. Nova busca constatou que a obra foi utilizada como referência na pós-graduação (três dissertações e uma tese), nos Grupos de Trabalho n. 15 – Educação Especial – e n. 20 – Psicologia da Educação – da ANPEd (uma pesquisa, três textos de discussão e aprofundamento) e em livros e periódicos (dois capítulos de livro, nove artigos publicados em periódicos) total de dezenove trabalhos. Dois destes referenciam a obra na formação de professores para atuação em Educação Especial ou atendimento educacional especializado, sugerindo ser esta, ainda, pouco disseminada na formação docente continuada. Palavras-chave: Defectologia; Política Nacional. Formação de Professores; Educação Especial.